Scan to BIM for the digital management and representation in 3D GIS environment of cultural heritage site. - Pepe, Massimiliano; Costantino, Domenica; Alfio, Vincenzo Saverio; Restuccia, Alfredo Garofalo; Papalino, Nicola Massimiliano (Journal of Cultural Heritage, 2021)
The aim of this paper is to implement a novel Scan to BIM method applied to cultural heritage field to build 3D GIS model able to connect different databases and, as consequence, allowing a multidisciplinary approach. The proposed method was applied to the case study of a rock church located in the famous ceramics district of Grottaglie (Italy). To obtain the 3D GIS model of the structure under investigation, it was necessary to perform, as a first step, an integrated survey with Terrestrial Laser Scanner technology and close range photogrammetry which allowed the construction of a dense point cloud and high-resolution orthophotos useful for the study of architectural and historical analysis of the elements present within the rock site. Subsequently, the single objects identified using the stratigraphic method, was modelled from point cloud by the development of an original procedure based on the use of some tools developed in Rhinoceros and MeshLAB software that allowed reconstructing the objects in a geometrically accurate way. Indeed, the difference between the point cloud and the BIM model was of few millimetres, demonstrating the high quality of the proposed method. Finally, the BIM model was imported into 3D GIS environment and for each element previously identified, it was possible to connect multi-information.